Diving and subaquatic medicine - Edmonds, Carl; Bennett, Michael; Lippmann, John; Mitchell, Simon J. (CRC Press, Taylor & Francis Group, 2016)
Considered an essential resource by many in the field, Diving and Subaquatic Medicine remains the leading text on diving medicine, written to fulfil the requirements of any general physician wishing to advise their patients appropriately when a diving trip is planned, for those accompanying diving expeditions or when a doctor is required to assess and treat anyone who has been involved in a diving accident. For this fifth edition the original author, Carl Edmonds, is joined by a new team of collaborators and the content has been entirely refreshed and updated throughout. Clinical cases, a feature popular with readers, are expanded, as is the illustrative content. Established and emerging diseases of diving medicine are all covered in full, as is the latest in types of diving, including free and indigenous diving, and associated equipment. Each medical disorder is discussed from a historical, etiological, clinical, pathological, preventative and therapeutic perspective in the informative and accessible style that has made previous editions so popular.